Sustainable city priorities in Global North versus Global South - Yazdani, Saeid; Dola, Kamariah (Canadian Center of Science and Education, 2013)
The paper sought to compare between the meaning of city sustainability concept in the Global North and Global South. The majority of existing sustainability concepts and goals, defined in developed countries, do not cover the main problems of cities in developing countries. While most of the sustainability discourses in industrialized countries refer to environmental issues, developing countries are still involved with economic and social matters such as poverty, social injustice, gender discrimination. Despite the fact that, the main part of climate change causes are produced in developed countries, people in developing countries are struggling with the negative effects of climate change. To put it more precisely, developing nations' citizens, who are not responsible for climate change, are climate change vulnerable populations. Based on a review of literature, this article concludes that, in the current global imbalance situation, a universal strategy “one size fit for all” of sustainability city cannot be applied to cities all around the world. Moreover, “inter-nations responsibility” is a missing key point in sustainability-related literature. To this end, it is necessary to revise the sustainability-related concepts in order to apply in the Global South.